Makro Ekonomi dan Return Saham: Suatu Telaah Pustaka di Indonesia - Herawati, Nurul; Bandi, Bandi (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2019)
This article aims to examine research related to macroeconomic variables that affect stock returns in Indonesia. The study was mapped from 25 research articles published in 20 nationally accredited scientific journals over a 18-year period. The research method used